New records of harvestman and description of a new species of Metaplatybunus (Opiliones, Phalangiidae) from Georgia - Chitadze, Beka; Bulbulashvili, Natalia; Snegovaya, Nataly (Zootaxa, 2025)
A new harvestman species of the family Phalangiidae, Metaplatybunus disputandus sp. nov. is diagnosed, illustrated, and described, based on male specimens from Georgia and N Caucasus. The first record of Amilenoides caucasicus Martens & Wijnhoven, 2022 in Georgia is presented. The first COI sequences of both species are provided for the first time.